PENDIDIKAN KLINIK SEBAGAI INSTRUMEN PENTING DALAM PEMBAHARUAN PENDIDIKAN HUKUM DI INDONESIA - Sahnan Sahuri Siregar; Otong Rosadi (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
The field of legal science as an applied science should have given birth to law graduates ready for combat to engage in the world of law in particular and community development in general. Be it as a lawyer, judge, prosecutor, notary, legal consultant as well as other legal professions. As one of the